Approaching the Scientific Method in Literary Studies: on the Notions of Framework and Method (and their Application to Kurt Vonnegut’s Slaughterhouse-Five) - Francisco Collado-Rodríguez (Miscelánea: A Journal of English and American Studies, 2016)
Mostly addressed to novice scholars and instructors, this paper discusses some of the implications that the concepts of Theoretical Framework and Method of Analysis have for the field of Literary Studies. The limits between the two notions are unclear, which may lead to inconsistent teaching results or rejection of research proposals. The paper suggests a tentative definition for these yet unresolved conceptual issues. Then, it provides an example of the working of framework and method applied to Vonnegut’s novel Slaughterhouse-Five. Stress is given to the fact that in Literary Studies the frame and method deployed by the scholar should not be confused with the frame and method used by the author whose work constitutes the corpus of analysis.